Measuring and Maximizing the Effectiveness of Honor Codes in Online Courses - Corrigan-Gibbs, Henry; Cutrell, Ed; Gupta, Nakull; Thies, Bill; Northcutt, Curtis (2015)
We measure the effectiveness of a traditional honor code at deterring cheating in an online examination, and we compare it to that of a stern warning. Through experimental evaluation in a 409-student online course, we find that a pre-task warning leads to a significant decrease in the rate of cheating while an honor code has a smaller (non-significant) effect. Unlike much prior work, we measure the rate of cheating directly and we do not rely on potentially inaccurate post-examination surveys. Our findings demonstrate that replacing traditional honor codes with warnings could be a simple and effective way to deter cheating in online courses.